DIET IN DERMATOLOGY: PRESENT PERSPECTIVES - Basavaraj, K H (Medknow Publications, 2010)
Many nutrients are essential for life, and an adequate amount of nutrients in the diet is necessary for providing energy, building and maintaining body organs, and for various metabolic processes. The role of food in the induction of various skin disorders and skin diseases leading to nutritional deficiencies is well known. The photo-protective potential of antioxidants, the effects of micronutrient supplementation on the skin immune system, and the modulating effects of fatty acids on skin disorders are well documented. Skin diseases due to nutritional deficiencies, the dietary role in skin immunity and various skin diseases, and the role of antioxidants and other supplements in skin health have been reviewed.